Preserving Local Writers, Genealogy, Photographs, Newspapers, and Related Materials - Smallwood, Carol; Williams, Elaine (Rowman & Littlefield Publishers, 2012)
Preservation of historical documents and library related materials is a growing problem in all library types and institutions. Fortunately, editors Carol Smallwood and Elaine Williams have pulled together the wisdom of practicing professionals to elucidate how to cope with the many problems that arise when preserving, managing, and digitizing important collections. Preserving Local Writers, Genealogy, Photographs, Newspapers, and Related Materials contains informative chapters on physical preservation, collection management, cooperation with organizations and communities, various formats, and special projects. Each part covers the preservation of specific materials, from newspapers and scrapbooks to photographs and oral histories. In addition, chapters cover repair and restoration of materials, while taking into consideration the current state of funding for agencies with an interest in history. Contributors also shed light on how the racial, economic, and political dynamics of the past affect how collections are gathered, maintained, and presented today. Preserving Local Writers, Genealogy, Photographs, Newspapers, and Related Materials offers plenty to inspire anyone facing backlogs of unprocessed papers or boxes of artifacts. Stories of the rescue efforts of a group of volunteers, or the discovery of a lost diary, show that the hard work of preservation is well worth it. Libraries, archives, and historical and genealogical societies all have their role to play in preserving important historical materials, as do patrons, sponsors, and volunteers; such institutions and individuals will find this book extremely helpful in their preservation efforts.